Clinical exercise physiology - Ehrman, Jonathan K. 1962- editor; Gordon, Paul M. 1960- editor; Visich, Paul S. 1955- editor; Keteyian, Steven J., editor (Champaign, IL Human Kinetics, 2019)
As the most comprehensive resource of its kind, Clinical Exercise Physiology, Fourth Edition, thoroughly examines the effects of exercise on chronic disease. It investigates 24 conditions, covering the scope of each disease as well as the pathophysiology, medications, and clinical applications. It also examines clinical considerations and exercise prescriptions for four special populations.
Includes bibliographical references (pages 635-736) and index.
Keywords: Exercise therapy; Clinical exercise physiology